2004
DOI: 10.1021/ja0495359
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Proteolytic Activity of Anthrax Lethal Factor by Aminoglycosides

Abstract: The anthrax lethal factor (LF), a Zn-dependent endopeptidase, is considered the dominant virulence factor of anthrax. Because pharmacological inhibition of the catalytic activity of LF is considered a plausible mechanism for preventing the lethality of anthrax, a high-throughput screening experiment based on LF-catalyzed cleavage of a fluorescent substrate was performed to identify novel inhibitors of LF. The RNA-targeting antibiotics, neomycin B and some synthetic dimeric aminoglycosides, were found to be nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0
1

Year Published

2004
2004
2007
2007

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 14 publications
2
48
0
1
Order By: Relevance
“…A cooperative effect between an anti-LF and an anti-PA antibody has been described previously (7), so we looked for such cooperation between 2LF and our anti-PA Fab, 35PA 83 (26). The assays were performed in vitro, because not enough Fab was available for in vivo tests.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A cooperative effect between an anti-LF and an anti-PA antibody has been described previously (7), so we looked for such cooperation between 2LF and our anti-PA Fab, 35PA 83 (26). The assays were performed in vitro, because not enough Fab was available for in vivo tests.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, and because a cooperative effect between an anti-LF and an anti-PA antibody has already been described in vivo (6), we have developed an anti-LF scFv which is apparently the first recombinant antibody fragment of this specificity ever obtained. This contrasts with both (i) the large number of anti-PA antibodies that have been developed (17,36,38,50,56), sometimes by exploiting the availability of lymphocyte donors immunized with anthrax vaccines composed mainly of PA, and (ii) the many synthetic molecules that have been developed to inhibit the enzymatic (proteolytic) activity of LF (15,24,26,32,37,42,52,55) but whose bioavailability and tolerance are not guaranteed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FRET studies using small peptides demonstrated 100-fold faster cleavage of a consensus cleavage sequence (derived from MAPKK cleavage sites) when compared with natural sites (8). Using FRET peptides, small molecule inhibitors with K i 's ranging from 0.5 lM to 7 nM have been isolated (13,14). Absorbance methods using p-nitroanilide coupled peptides in HTS screens were used to select the peptide inhibitor IN-2-LF (9).…”
mentioning
confidence: 99%
“…Interestingly, several natural products, including defensin peptides [33; 34] and aminoglycosides [35], have been recently shown to inactivate LF factor.…”
Section: Introductionmentioning
confidence: 99%